2003
DOI: 10.1046/j.1439-0507.2003.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomembranous tracheobronchial aspergillosis: a rare manifestation of invasive aspergillosis in a non‐neutropenic patient with Hodgkin's disease

Abstract: Pseudomembranous tracheobronchial aspergillosis coincident with systemic pulmonary aspergillosis represents a rare manifestation of fungal infection in immunocompromized hosts. We report on a patient with recurrent Hodgkin's disease, showing this infectious pattern after treatment with corticosteroids within the antineoplastic schedule, whereas neutropenia--the main risk factor for mold infections--had not occurred. An impaired number of helper T lymphocytes was merely detected as an additional, but hypothetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A few species are involved in different human mycoses, although these fungi are normally considered common contaminants: in immunosuppressed patients, especially Aspergillus fumigatus and Aspergillus flavus may cause pulmonary aspergillosis, invasive aspergillosis and occasionally pseudomembranous tracheobronchial aspergillosis [16]. Aspergilloma can be observed in immunocompetent patients with pre-existing lung cavities.…”
Section: Discussionmentioning
confidence: 99%
“…A few species are involved in different human mycoses, although these fungi are normally considered common contaminants: in immunosuppressed patients, especially Aspergillus fumigatus and Aspergillus flavus may cause pulmonary aspergillosis, invasive aspergillosis and occasionally pseudomembranous tracheobronchial aspergillosis [16]. Aspergilloma can be observed in immunocompetent patients with pre-existing lung cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Arriero et al found simultaneous obstructive and pseudomembranous necrotizing tracheobronchitis due to Aspergillus flavus in a diabetic patient with ALL [67]. Buchheidt et al reported a patient with Hodgkin lymphoma and pseudomembranous form of tracheobronchial aspergillosis in whom patchy ulcerations were also found in the trachea and bronchi [68]. Van Assen et al described “yellowish plaques, ulcerations and pseudomembranes” seen during bronchoscopy in a patient who underwent hematopoietic stem cell transplantation (HSCT) due to acute myeloid leukemia (AML) and who subsequently developed Aspergillus tracheobronchitis [69].…”
Section: Trachobronchial Aspergillosismentioning
confidence: 99%
“…Dyspnea, inspiratory wheezes, fever, and nonproductive cough belong to the most commonly reported symptoms [66, 6870]. Airway obstruction may result in atelectasis and severe respiratory failure [72].…”
Section: Trachobronchial Aspergillosismentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the English literature, we recognized that the most common agents causing EBFI are Aspergillus spp. [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], Coccidioides immitis [46] , agents of zygomycosis [6,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73], Candida spp. [6, 34,74,75,76], Cryptococcus neoformans [77,78,79,80,81,82,83,84,85,86,87,88], and Histoplasma capsulatum [89,…”
Section: Introductionmentioning
confidence: 99%